Blade optimal design parameters determination - N. T. Surashov; R. B. Asmatulaev; D. N. Tolymbek (Вестник СибАДИ, 2022)
Introduction. In Kazakhstan in present time there is a large number of earthmoving works, which leads to an increase in the demand for earthmoving-transport machines (ETM), in particular bulldozers of different types. In various industries and construction projects, the fleet of foreign-made ETM is operated and constantly updated, including the CIS countries (Russia, Belarus, Ukraine, etc.) in various type-sizes. So at construction sites, including the construction of roads and railways, bulldozers are widely used: Caterpillar Corporation such as Cat (USA), Liebheer (Germany), Xuanhua Construction machinery Co, Ltd (HBXG) and ZoomLion and Shehwa (China); bulldozers ChTZ-UralTRAK (Russia), etc.The construction of roads and railways with a length of several thousand kilometers is impossible to imagine without the participation of a universal bulldozer. One of the most important components of the bulldozer is the working organ (WO) of the bulldozer.The performance of the bulldozer largely depends on what type of blade is installed on it. Capacity (maximum prism of drawing the soil) is one of the main characteristics determined by the height and width of the blade, and most manufacturers offer add-ons (visor) that makes it possible to increase the height of the blade. Increasing the blade height allows more material to be moved and reduces spillage through the top of the blade. On the other hand, increasing the volume of the drawing prism along the width of the blade is offered by the side cheeks, giving the blade the shape of a bucket. They do not allow the moving soil to fall out on the sides of the blade (side rollers), thereby increasing the volume of material being moved. However, an excessive increase in blade capacity will require additional power costs of the bulldozer during operation, which will cause an increase in loads on the machine components and accelerate the intensity of their wear, especially when the bulldozer moves up the slope.The volume of material moved by the blade in one pass depends, in addition, on the possibility of changing the angle of the blade relative to the vertical and horizontal plane. In modern blade designs, the positions of the angle of inclination are regulated by 4 or 6 positions, depending on the category of soil being developed. The purpose of this study is to optimize the geometric parameters and establish the trapezoidal shape of the blade, taking into account the interaction of its frontal surface with the formed maximum prism of drawing the soil.Materials and methods. As materials, the developed soil and the bulldozer blade were used, the process of their interaction was investigated with the maximum formation of the prism of drawing the soil before the dump, using the graphic-analytical method of research.Results. The process of interaction of the blade with the soil has been optimized by graphic-analytical means, the maximum (maximum permissible) parameters of the blade have been determined, taking into account the traction factor of the bulldozer and the category of the soil being developed.Discussion and conclusion. Until now, the geometric shapes of promising designs of the bulldozer blade were installed mainly by experimental means, without taking into account the contact of the blade area with the ground. Methods for determining the rational shape of the blade have not been developed, especially the theoretically grounded optimal parameters of the WO, taking into account the touch of the longitudinal section of the soil from the frontal surface of the blade. Methods for determining the optimal (adapted) shapes and geometric parameters of the WO were not developed, taking into account the contact of the frontal surface of the blade with the maximum drawing prism. Methods for calculating the optimal parameters of the perspective blade design adapted to the developed soil are proposed:– rational geometric shapes of both the frontal and cross-section of the blade are determined;– mathematical formulas for determining the optimal parameters of the new blade design are presented, namely:the height of the blade and the visor; width of the blade, visor and additional knife-extender;– defined: the perimeter of the blade, the width and height of the side roller, when forming the maximum prism of drawing the soil in front of the blade.